PROTECTIVE EFFECTS OF VORTIOXETINE IN PREDATOR SCENT STRESS MODEL OF POST-TRAUMATIC STRESS DISORDER IN RATS: ROLE ON NEUROPLASTICITY AND APOPTOSIS - YAVUZ, AYŞE NUR; ÖZBEYLİ, DİLEK; ŞENER, GÖKSEL; ÖZKAN YENAL, NAZİYE (POLISH PHYSIOLOGICAL SOC, 2019)
Post-traumatic stress disorder (PTSD) can be observed after a traumatic event. The effect of an antidepressant vortioxetine (Vrx) against PTSD is unknown. The aim of this study was to investigate the possible protective effect of Vrx in the predator scent-induced PTSD rat model. The rats were exposed to dirty cat litter for 10 min and the protocol was repeated 1 week later with clean cat litter as a trauma reminder. The rats received Vrx (10 mg/kg/p.o.) or saline (1 ml/kg/p.o.) during 7 days between two exposure sessions. Novel object recognition test, hole board test, and elevated plus maze were performed. The b-cell lymphoma (bcl-2)/bcl-2-associated X protein (bax) ratio, brain-derived neurotrophic factor (BDNF), caspase-3 and -9 expressions were detected using Western blotting in the amygdaloid complex, hippocampus, and frontal cortex. Our results indicate that increased freezing time and anxiety index in the stress-induced group is decreased with Vrx application. Vrx treatment improved deteriorated recognition memory in the stress-induced group. Decreased bcl-2/bax ratio and BDNF level and increased caspase-3 and -9 expressions in the stress group, improved with Vrx in the amygdala, and hippocampus. Decreased bcl-2/bax ratio and increased casp-3 and -9 expressions in the stress group are ameliorated with Vrx in frontal cortex. The level of BDNF was increased with Vrx in the frontal cortex. Increased damage scores in the amygdaloid complex, hippocampal CA3, and frontal cortex in the stress group ameliorated with Vrx treatment. Our results show that if vortioxetine is administered immediately after trauma, it reduces anxiety, cognitive and neuronal impairment and may be protective against the development of PTSD.
Keywords: post-traumatic stress disorder; vortioxetine; brain-derived neurotrophic factor; apoptosis; recognition memory; GENERALIZED ANXIETY DISORDER; MULTIMODAL ANTIDEPRESSANT; ANIMAL-MODEL; HIPPOCAMPAL VOLUME; RECEPTOR SUBTYPES; LU AA21004; MEMORY; EXERCISE; EXPOSURE; AMYGDALA